Macroeconomic fundamentals and exchange rates in South Asian economies: Evidence from pooled and panel estimations. Issue 2 (17th June 2019) - Draz, Muhammad Umar; Ahmad, Fayyaz; Gupta, Bhumika; Amin, Waqas
Abstract : Purpose: This study aims to examine the impact of macroeconomic fundamentals on exchange rates of selected South Asian economies during 1981-2013. Design/methodology/approach: The authors have used two econometric approaches to the data. For the pooled sample, estimated generalized least square (EGLS) and the two-stage least square method are applied. For the panel data, the authors have used the panel generalized method of moments and ordinary least squares (OLS) methods. Findings: The results suggest that macroeconomic factors have a significant impact on exchange rates. The robust findings highlight that improvements in domestic economic and political systems are crucial for a successful exchange rate policy. Originality/value: The existing literature on exchange rate fundamentals have either focused on exchange rates and international trade or investigated the relationship for the developed economies. Covering a period of more than three decades, and using both pooled and panel estimations, our study is unique in terms of its focus on the South Asian economies.